Cryptococcus gattii infection in solid organ transplant recipients: description of Oregon outbreak cases. Issue 3 (19th May 2015) - Forrest, G.N.; Bhalla, P.; DeBess, E.E.; Winthrop, K.L.; Lockhart, S.R.; Mohammadi, J.; Cieslak, P.R.
Abstract Cryptococcus gattii was recognized as an emerging infection in the Pacific Northwest in 2004. Out of 62 total infections in Oregon since the outbreak, 11 were in solid organ transplant (SOT) recipients. SOT recipients were more likely to have disseminated disease and higher mortality than normal hosts, who mostly had isolated mass lesions. The median time from transplantation to C. gattii diagnosis was 17.8 months. The primary sites of infection were lung (n = 4), central nervous system (n = 3), or both (n = 4). The Oregon‐endemic strain, VGII (subtypes IIa and IIc) was present in 10 of 11 patients; the median fluconazole minimum inhibitory concentration (MIC) was 12 μg/mL (range 2–32 μg/mL) for this strain. We found C. gattii infection among organ transplant recipients was disseminated at diagnosis, had low cerebrospinal fluid cryptococcal antigen titers, and was associated with an elevated fluconazole MIC and high attributable mortality.